Secondary electro-optic response induced by VOD875S dye in polymer stabilised liquid crystals. Issue 7 (27th May 2020) - Huai, He; Mu, Qihui; Li, Xiaoshuai; Ma, Hongmei; Sun, Yubao
ABSTRACT: Polymer stabilised liquid crystal, which has the scattering state and transparent state, is widely used in tunable optic devices. Here, we demonstrate a polymer stabilised liquid crystal device with secondary electro-optic response phenomenon. Doped VOD875S dye into the normal polymer stabilised liquid crystal, the transmittance of the scattering and transparent states is reduced; moreover, the transparent region can be extended beyond the electrode and the transmittance is increased again when the operating voltage is larger than a critical value. The effects of dye concentration, polyimide (PI) layer and surfactant concentration on the secondary electro-optic response phenomenon of PSLC film were studied. It was found that high dye concentration, no PI layer and high surfactant concentration can effectively reduce the critical voltage of the secondary electro-optic response phenomenon. The secondary electro-optic response phenomenon can be used in some smart devices. Graphical abstract: